Revitalisasi Kuliner Lokal Sebagai Brand dan Pilar Pariwisata Hijau Di Desa Bonjeruk - Hariani, Yuni Sulpia; Budiman; Anwariyah, Komariyuli (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
This study aims to analyze and explain the diversity of local culinary delights that are used as brands and pillars of green tourism in Bonjeruk Tourism Village, Central Lombok Regency. The relationship between local culinary delights as brands of tourism villages and pillars of green tourism in Bonjeruk Tourism Village is like a coin with two sides. Local culinary delights in Bonjeruk Tourism Village utilize vegetables and spices grown in local fields and to meet the needs of culinary ingredients, replanting becomes a cycle of preservation that has a positive impact on the environment and also local economic growth. This study is a study that uses qualitative methods. Data collection was carried out using observation techniques, in-depth interviews and documentation. The results of this study indicate that there are a number of local culinary delights in Bonjeruk Tourism Village that are used as brands and pillars of green tourism. Local culinary delights include food and drinks that are used as brands and pillars of green tourism such as ayam merangkat, sate kuncung, olah-olah sayur, olah-olah daging, ares, serebuk, pelecing, jejeruk, bebetok, raon, ebatan, tum and jamu sherbet. The local cuisine of Bonjeruk Tourism Village is unique, evident in the use of ingredients and the cultural stories behind each type of local food and drink, distinguishing it from local cuisine from other villages or regions on Lombok Island. This uniqueness is the reason local cuisine is used as a tourist attraction and brand in Bonjeruk Tourism Village. Furthermore, the use of local cuisine as a village tourism brand has a positive impact on environmental conservation, marked by the replanting of various types of plants used as raw materials for local cuisine that are almost extinct. By being studied and re-popularized as a tourism village brand, local cuisine becomes a promotional tool for green tourism, which is expected to increase the number of tourist visits, improve the community's economy, and preserve the local environment.